Viral etiology of severe acute respiratory infections in hospitalized patients, Shandong, China - Chunwang Li; Yujie He; Xiao Pan; Huimin Yin; Yaowen Pei; Shaoxia Song; Lin Sun; Shu Zhang; Julong Wu; Zhong Li; Xianjun Wang; Zengqiang Kou; et al. (PLoS ONE, 2025)
Background Severe Acute Respiratory Infection (SARI) represents a critical global public health challenge, accounting for substantial severe morbidity and hospitalization burdens with distinct geographical patterns in etiological profiles. This study systematically characterizes the epidemiological and clinical phenotypes of SARI patients in Shouguang county, Shandong Province, China. Methods A prospective observational study was conducted at Shouguang People’s Hospital between August 28, 2023 and April 30, 2024, enrolling 1,730 hospitalized patients with SARI from the Departments of Infectious Diseases and Respiratory and Critical Care Medicine. Standardized electronic case report forms were used to systematically collect the demographic characteristics, clinical manifestations and laboratory testing results. Oropharyngeal swab specimens were collected within 24 hours of admission for each patient and stored at −80°C. Multiplex real-time quantitative PCR (RT-qPCR) was performed using the ABI 7500 system to detect 11 respiratory viruses infection, including influenza A virus (IFA), influenza B virus (IFB), respiratory syncytial virus (RSV), parainfluenza virus (HPIV), human coronaviruses (HCoV), human metapneumovirus (HMPV), rhinovirus (HRV), enterovirus (EV), human bocavirus (HBoV), human adenovirus (HAdV), and SARS-CoV-2 (COVID-19). Results 501 samples (28.96%) were tested positive for at least one virus. The most frequently detected viruses and their infection rates were as follows: IFA (11.33%), COVID-19 (6.53%), HPIV (2.31%), HCoV (2.20%), RSV (1.79%), IFB (1.68%), HMPV (1.56%), EV (0.64%), HADV (0.52%), and HBoV (0.06%). Among patients aged 0–14 years, IFA and EV had the highest infection rates, both at 9.46% (7/74). In the 15–24 age group, IFA exhibited the highest infection rate at 19.70% (26/132). In patients aged ≥70 years, COVID-19 was the most frequently detected virus, with a infection rate of 10.69% (65/608). The overall virus infection rate peaked at 60.00% (30/50) in epidemiological week 48 of 2023. During weeks 46–50 of 2023, the overall infection rate remained consistently high (range: 28.42–60.00%). Significant differences in infection rates were observed across hospital departments (χ² = 5.52, P < 0.05), The Department of Infectious Diseases demonstrated a higher infection rate of 34.91% (162/464) compared to 29.07% (368/1266) in the Department of Respiratory Medicine. Conclusion Viral etiological analysis of SARI patients in Eastern China identified IFA, COVID-19, and HPIV as the three predominant virus, with influenza virus exhibiting the highest frequency of co-infection with other respiratory viruses. Our study further revealed significant heterogeneity in virus distribution across different hospital departments, age groups, and admission periods. The most common clinical manifestations were cough and fever, with distinct symptomatic profiles observed among infections caused by different viruss. These findings provide scientific evidence to inform government strategies for optimizing the prevention and management of respiratory infectious diseases.